1990
DOI: 10.1007/bf00869842
|View full text |Cite
|
Sign up to set email alerts
|

The 1989 report of the North American Pediatric Renal Transplant Cooperative Study

Abstract: This report of the North American Pediatric Transplant Cooperative Study summarizes data contributed by 57 participating centers on 754 children with 761 transplants from 1 January 1989 to 16 February 1989. Data collection was initiated in October 1987 and follow-up of all patients is ongoing. Transplant frequency increased with age; 24% of the patients were less than 5 years, with 7% being under 2 years. Common frequent diagnoses were: aplastic/dysplastic kidneys (18%), obstructive uropathy (16%), and focal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(40 citation statements)
references
References 0 publications
1
39
0
Order By: Relevance
“…Data collection methods have been described previously (5). Briefly, extensive data are collected at the time of enrollment, at 1 month post-transplantation, at 6 months post-transplantation, and at every 6 months thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…Data collection methods have been described previously (5). Briefly, extensive data are collected at the time of enrollment, at 1 month post-transplantation, at 6 months post-transplantation, and at every 6 months thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…Although data from the pediatric population are not available, however, certain inferences can be made from the North American Pediatric Renal Transplant Cooperative Study [9]. The Registry (1987)(1988)(1989) reported that black and Hispanic children accounted for 23% of all kidney transplants but 38% of renal transplants in which FSGS was the cause of ESRD [9]. These findings suggested that black and Hispanic children experience a disproportionate frequency of FSGS with progression to ESRD, hence we analyzed our Single-center experience of FSGS comparing white arid non,white children.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of ESRD in non-white patients was 2.7 times higher than in white patients in a national survey [8]. Although data from the pediatric population are not available, however, certain inferences can be made from the North American Pediatric Renal Transplant Cooperative Study [9]. The Registry (1987)(1988)(1989) reported that black and Hispanic children accounted for 23% of all kidney transplants but 38% of renal transplants in which FSGS was the cause of ESRD [9].…”
Section: Introductionmentioning
confidence: 99%
“…256 The probability of developing ESRD for children who experienced PRS was based on registry data. 257 The age at which children will develop ESRD is uncertain; therefore, this is represented by a distribution of ages (7-24 years) based on evidence reported in two observational studies. 258,259 Two consequences of ESRD are considered, transplant and long-term home dialysis.…”
Section: Long-term Costs and Effects From The Long-term Modelmentioning
confidence: 99%